Ecological relevance of anabranch confluences: Hydrological and morphological effects. Issue 2 (29th January 2019) - Blettler, Martín C. M.; Amsler, Mario L.; Espinola, Luis A.; Rabuffetti, Ana Pía; De Drago, Ines Ezcurra; Drago, Edmundo E.
Abstract: The aim of the current study was to determine the ecological role of anabranch confluences at diverse hydrological regimes, taking into consideration the floodplain secondary channels of a large river as a case of study. In conducting this study, we used unpublished data from sampling campaigns performed in the past. Triplicate benthic sediment samples were taken at each station using a bottom grab and according to sampling protocols equal to the current ones. Benthic taxa were identified at the species and genus levels. According to our results, a protracted effect by the El Niño–Southern Oscillation (ENSO) phenomenon on benthic fauna structure was evident. This effect was observed not only in the confluences but also all along the rivers, reflecting its ecological effect at least 1.5 years after its occurrence. Thus, the ENSO effect on benthic organisms should not be treated like a "physical action–reaction" but rather as an ecological relationship with lag periods ("ecological inertia") after its occurrence. On the other hand, one of the studied confluences was categorized as a "hydro‐geomorphic patch" along the river channel, resulting from shifts in hydraulic and sedimentological conditions, which are explained by local morphological features. This hydro‐geomorphic patch created a critical site of abrupt changes in ecological patterns, enhancing the biodiversity of the river system. However, this hydro‐geomorphic patch was not detected in another anabranch confluence, where the benthic assemblage was comparable with that recorded in straight sections. Accordingly, we concluded that the mere presence of an anabranch confluence is not a sufficient reason to assume enhancing local habitat heterogeneity or biodiversity.